2009
DOI: 10.1111/j.1525-1470.2009.00974.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Efficacy, Safety, and Acceptability of Imiquimod 5% Cream versus Cryotherapy for Molluscum Contagiosum in Children

Abstract: To compare the efficacy, safety and acceptability of imiquimod (IMQ) 5% cream with cryotherapy for the treatment of molluscum contagiosum (MC) in children. Prospective, randomized, comparative, observer blinded study. A total of 74 children, with MC were divided randomly to receive treatment with either IMQ 5% cream (group A) 5 days a week or cryotherapy (group B) once a week until clinical cure or up to a maximum of 16 weeks. All the patients were followed up weekly during active treatment. The patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 20 publications
(20 reference statements)
1
34
0
10
Order By: Relevance
“…Moreover, RCTs of imiquimod for MC in children continue to be designed, conducted, and reported without reference to the 2 BPCA RCTs. 6 This is not the first time that publication of studies conducted under BPCA or similar programs has been found lacking. One study found that only 44% of such studies were published in an indexed, peer-reviewed journal.…”
mentioning
confidence: 99%
“…Moreover, RCTs of imiquimod for MC in children continue to be designed, conducted, and reported without reference to the 2 BPCA RCTs. 6 This is not the first time that publication of studies conducted under BPCA or similar programs has been found lacking. One study found that only 44% of such studies were published in an indexed, peer-reviewed journal.…”
mentioning
confidence: 99%
“…18 No entanto, apesar da cirurgia dermatológica ser extremamente segura e com baixo risco de complicações, os procedimentos cirúrgicos estão sujeitos a infecções, hemorragias, hematomas ou alterações da pressão arterial. 34 O imiquimod 5% creme, alvo de grandes discussões e divergências literárias, 15,16,[19][20][21][22] …”
Section: Discussionunclassified
“…O estudo por Al-Mutairi et al 15 relatou proporção de cura de 100% com 1 sessão por semana até a cura ou em um máximo de 16 semanas. O tempo de resolução das lesões foi em média três a seis semanas, sendo a técnica mais barata que outros métodos, como o imiquimod.…”
Section: Características Dos Estudos Relatados Nos Artigos E a Classiunclassified
“…(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) So an atopic dermatitis that is not properly treated, can lead to the insurgence of the virus of the molluscum contagiosum.Signs and symptoms of molluscum contagiosum include bumps on the skin that are raised, round and flesh coloured, small -typically under about 1/4 inch in diameter, they characteristically have a small indentation (umbilication) or dot at the top near the center. They become red and inflamed and itchy and therefore may be easily removed by simple scratching or rubbing, which can spread the virus to adjacent skin.…”
Section: Introductionmentioning
confidence: 99%